2022
DOI: 10.1111/pde.14936
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel variant of FOXP3 resulting in severe immune dysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome highlights potential pitfalls of molecular testing

Abstract: Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare genetic disorder that typically presents in the first year of life with severe diarrhea, autoimmune endocrine disorder, and inflammatory dermatitis, most commonly an eczematous dermatitis. IPEX syndrome is caused by variants in the FOXP3 gene leading to dysregulation of T-regulatory (Treg) cells and an aberrant immune response. Here, we present a case of severe IPEX syndrome diagnosed following whole genome sequencing (WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, several studies have shown that the FOXP3 gene is not essential for the establishment of the Treg cell lineage, but rather for its suppressive effector functions, as it controls the expression of different regulatory molecules such as TIGIT, CTLA-4, and the suppression of the IL-2 gene and different effector T-cell cytokines ( 59 61 ). Reported mutations causing IPEX are null or nonsense variants and small deletions or insertions in the reading frame ( 62 64 ) in the FOXP3 gene that result in a residual expression of the protein, but lacking function. Therefore, Treg cells from these patients are dysfunctional, being unable to inhibit the proliferation and inflammatory functions of effector T cells (Teff) ( 62 , 65 , 66 ).…”
Section: Iei and Treg: The New Kid On The Blockmentioning
confidence: 99%
“…However, several studies have shown that the FOXP3 gene is not essential for the establishment of the Treg cell lineage, but rather for its suppressive effector functions, as it controls the expression of different regulatory molecules such as TIGIT, CTLA-4, and the suppression of the IL-2 gene and different effector T-cell cytokines ( 59 61 ). Reported mutations causing IPEX are null or nonsense variants and small deletions or insertions in the reading frame ( 62 64 ) in the FOXP3 gene that result in a residual expression of the protein, but lacking function. Therefore, Treg cells from these patients are dysfunctional, being unable to inhibit the proliferation and inflammatory functions of effector T cells (Teff) ( 62 , 65 , 66 ).…”
Section: Iei and Treg: The New Kid On The Blockmentioning
confidence: 99%